1971
DOI: 10.1021/es60048a005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of crude and residual-type oils by fluorescence spectroscopy

Abstract: The ability to pinpoint the source of an oil spill on water is vital to the enforcement of water pollution control procedures and to the reduction in frequency of spills. The usual approach to identifying the source of a spill is the analysis of numerous parameters that can be used to compare samples of oil from the spill to those from suspected sources. A method was developed to determine fluorescence intensities and wave number ratios for comparing various crude and residual-type oils. The method was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…This fact has been known since the 1970s [2][3][4] and later studies have only confirmed it. The differences concern the shapes of the spectra, intensity and spectral area of the phenomenon, and are clear in the cases of different crude oils and various types of petroleum.…”
Section: Introductionmentioning
confidence: 92%
“…This fact has been known since the 1970s [2][3][4] and later studies have only confirmed it. The differences concern the shapes of the spectra, intensity and spectral area of the phenomenon, and are clear in the cases of different crude oils and various types of petroleum.…”
Section: Introductionmentioning
confidence: 92%
“…A very interesting example of an application to water pollution is the use of fluorescence spectra as a "fingerprint" for the identification of crude oils and other petroleum materials in oil spills. The technique suggested by Thruston and Knight (73) seems to be at least as reliable as conventional identification procedures and has led to further development of the technique by the Coast Guard and others.…”
Section: Air and Water Pollutionmentioning
confidence: 99%
“…All samples were analyzed within 24 h of elution from the resin column. Identification of the dominant oil hydrocarbons in the extracts was accomplished by comparing the maximum excitation and emission wavelengths of the sample with those observed for dilutions (in hexane) of authentic refined oil products (15,20). Maximum excitation wavelengths for gasoline, diesel fuel, and outboard oil were 278, 285, and 295 nm, respectively.…”
Section: Vol 32 1976mentioning
confidence: 99%